The Relationship between Students' Reading Attitude with the Result of Reading Comprehension - Muhammad Farhan Rafi; Aang Fatihul Islam; Dian Anik Cahyani (Universitas Pendidikan Mandalika, 2021)
Reading is a very important activity to get abundant information and add new knowledge. As students, reading activities have a very dominant role because they are required to be more scientific and rational in giving opinions or providing information both in oral and written. Besides, students' attitudes towards reading also have an important role. This study focused on their English reading comprehension and attitudes towards reading in English. This study aims to determine whether there is a significant relationship between students' attitudes with the result of reading comprehension. Data was collected by distributing questionnaires and reading comprehension tests for students of STKIP PGRI Jombang in the English Education Study Program. The Pearson Coefficient Product Moment is used to determine whether there is a significant relationship between students' attitudes with the result of reading comprehension. From the results found from the SPSS 16 application with a sample of 63 students in the 2019 class, there is a correlation of 0.478. These result indicates that students' reading attitudes are positively related to their reading comprehension. Thus, students must continue to read to improve their English reading skill.